Efeitos dos regimes de operação de reservatórios na transferência de energia em cadeias alimentares de peixes neotropicais - Gomes, Louise Cristina (2015)
1. The size spectrum associates the abundance of individuals with the size of their body. The main objective was to investigate the influence of reservoir operation regime on the process of energy transfer in fishes assemblage, testing the hypothesis that the reservoir operation modify the spatial variability of the slopes of the size spectra. 2. For this, samples were carried out the period from January 2005 to December 2007. Data were obtained in eight reservoir with different operation regime, located in the state of Paraná, southern Brazil. To calculate the slopes of fish size spectra we used Pareto I model. The effects of operation regime on the size spectra were evaluate from the paired t test. 3. The results showed that the reservoir operation regime presents significant effect on the size spectra of the fish assemblages, wherein the slopes of spectra indicated that the reservoirs tend to present higher proportions of the small individuals. This effect were more pronounced in the reservoirs that operate in accumulation, indicating less efficient energy transfer through food webs in these environments